The sociology of citizenship within socio-cultural contexts: a reinterpretation of identity and civic participation - Ramadhan, Iwan; Dewantara, Jagad Aditya (Universitas Tanjungpura, 2025)
This editorial concludes with a call to academics, researchers, and education practitioners to develop a sociology of citizenship rooted in Indonesia